Attitudes to Use of Mobile Banking and Demographic Factors - Saadah, Lailatus; Shafira, Alvina Laili (International Research-Based Education Journal, 2023)
This study intends to examine variations in attitudes toward using mobile banking among students at the University of KH. A. Wahab Hasbullah's economics faculty. This study employed a quantitative research design, and 37 respondents—students who use mobile banking at the banks of BCA, BRI, BSI, BNI, Mandiri, and Bank Jatim—were given questionnaires to complete. Descriptive analysis, attitude tabulation, and one-way ANOVA analysis are the data analysis methods used in this study. The findings of this study show that, among the 37 respondents that participated in the attitude tabulation, 19 respondents had favorable attitudes and 18 respondents had negative attitudes regarding using mobile banking. This demonstrates that the majority of respondents are happy with the services offered by all popular mobile banking platforms. Additionally, the findings of the one-way ANOVA analysis indicate that there is a probability value > 0.05 for the analysis of attitudes based on age, gender, occupation, and frequency of usage, so H0 is accepted and Ha is rejected. Therefore, views on using mobile banking are unaffected by factors such as age, gender, occupation, and frequency of use.